EFEKTIVITAS METODE PEER TEACHING TERHADAP SELF EFFICACY DAN KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA KELAS X DI SMA NEGERI 8 PANDEGLANG - Nurul Novianti; Jaka Wijaya Kusuma; Maulida Nur (LPPM Universitas Bina Bangsa, 2022)
This research was motivated by the tenth grade students at SMA Negeri 8 Pandeglang who lost their self-efficacy and lack of ability to understand mathematical concepts in mathematics. The purpose of this study is to determine the activities and learning processes using the peer teaching method, as well as to find out how much effective the peer teaching method is on self-efficacy and understanding of mathematical concepts for class X students at SMA Negeri 8 Pandeglang. This research is a descriptive qualitative research. The data collection techniques used were observation, questionnaires, students' mathematical concept understanding ability tests, and interviews, the research design was